Review of Journal of Institute of Science and Technology (JIST), Vol. 18 No. 1, 2013 - Singh, Nanda Bahadur (Journal of Institute of Science and Technology, 2015)
Journal of Institute of Science and Technology, 2014, 19(1): 160